2017
DOI: 10.1111/ajr.12396
|View full text |Cite
|
Sign up to set email alerts
|

Do programs for Aboriginal and Torres Strait Islander people leaving prison meet their health and social support needs?

Abstract: The objective of this review was to synthesise evidence on the health and social support needs of Aboriginal and Torres Strait Islander people leaving prison and on programs which aid successful community re-entry. A systematic literature review was undertaken of peer-reviewed and grey literature published between 2001 and 2013, focusing on the post-release needs of Aboriginal and Torres Strait Islander adults and pre-and post-release programs. Aboriginal and Torres Strait Islander people have high health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A substantial body of research has shown that the increasing number of Aboriginal women in prison is partly explained by their high rates of return to custody (Bartels, 2012), poor ‘throughcare’ (the continuous and coordinated management of people’s needs from the point of entering custody through to release), and lack of post-release support (Abbott et al, 2018; Baldry, 2010; Heffernan, Andersen, Davidson, & Kinner, 2015a; Lloyd et al, 2015; Shepherd, Ogloff, & Thomas, 2016). Incarcerated Aboriginal women in NSW are significantly more likely to have been previously incarcerated in comparison with non-Aboriginal women, to experience re-incarceration within 12 months of release from prison, and to be in prison on remand (unsentenced) (New South Wales Government Justice Health & Forensic Mental Health Network, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of research has shown that the increasing number of Aboriginal women in prison is partly explained by their high rates of return to custody (Bartels, 2012), poor ‘throughcare’ (the continuous and coordinated management of people’s needs from the point of entering custody through to release), and lack of post-release support (Abbott et al, 2018; Baldry, 2010; Heffernan, Andersen, Davidson, & Kinner, 2015a; Lloyd et al, 2015; Shepherd, Ogloff, & Thomas, 2016). Incarcerated Aboriginal women in NSW are significantly more likely to have been previously incarcerated in comparison with non-Aboriginal women, to experience re-incarceration within 12 months of release from prison, and to be in prison on remand (unsentenced) (New South Wales Government Justice Health & Forensic Mental Health Network, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander people in prison experience high levels of mental health problems, not only as a result of their time in prison, but also as a result of the continuing negative impacts of colonisation on individuals, families and communities (Abbott et al., 2018). Comorbid substance and non-substance mental health diagnoses in prisoners, unless appropriately treated, can lead to a substantial increase in reoffending once released from prison (Smith & Trimboli, 2010).…”
Section: The Benefits Of Arts-based Prison Programsmentioning
confidence: 99%
“…Such interventions tend to have higher participant engagement [47][48][49][50] and effectiveness. [51][52][53][54] Existing reviews of mental health interventions for prisoners or community offenders typically focus on the general population rather than on Indigenous or First Nations people, [55][56][57][58][59][60][61][62] and other reviews of interventions for vulnerable populations may include some Indigenous people or prisoners, but do not focus on Indigenous prisoners. [63][64][65][66] Only one Indigenous-specific review on prisoners was identified, but that focused on prisoners' needs when transitioning back to the community, rather than on interventions for Indigenous prisoners more generally.…”
Section: Introductionmentioning
confidence: 99%
“…[63][64][65][66] Only one Indigenous-specific review on prisoners was identified, but that focused on prisoners' needs when transitioning back to the community, rather than on interventions for Indigenous prisoners more generally. 55…”
Section: Introductionmentioning
confidence: 99%